Personality disorder: A new global perspective - Tyrer, Peter (2010)
Personality disorder is now being accepted as an important condition in mainstream psychiatry across the world. Although it often remains unrecognized in ordinary practice, research studies have shown it is common, creates considerable morbidity, is associated with high costs to services and to society, and interferes, usually negatively, with progress in the treatment of other mental disorders. We now have evidence that personality disorder, as currently classified, affects around 6% of the world population, and the differences between countries show no consistent variation. We are also getting increasing evidence that some treatments, mainly psychological, are of value in this group of disorders. What is now needed is a new classification that is of greater value to clinicians, and the WPA Section on Personality Disorders is currently undertaking this task.